Pengaruh Kompos Isi Rumen Sapidan Pupuk NPK terhadap Pertumbuhandan Produksi CabaiMerah (Capsicum annuum L.) - Anggraini, Mia; Ardian, Ardian; Ariani, Erlida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research aims to examine the effect of interaction of cow rumen compost with NPK fertilizer and get the best treatment combination in increasing the growth and yield of red chili pepper (Capsicum annuum L.). The research was conducted at Experimental Garden of Faculty of Agriculture Universitas Riau from September 2018 to January 2019.The research was done in a completely randomized design (CRD) factorial and repeated three times. The first treatment was cow rumen compost that consist of 3 levels that are 10 ton.ha-1, 15 ton.ha-1 and 20 ton.ha-1. The second factor was NPK fertilizer that consist of 3 levels that are 600 kg.ha-1, 900 kg.ha-1 and 1200 kg.ha-1. The observation parameters were plant height, dichotomous height, stem diameter, age of flowering, age of the harvest crop, fruit length, fruit diameter, number of fruits per plant and fruit weight per m2. The research data wereÂ analyzed using analysis of varriance (ANOVA) and followed by duncanâ€™s new multiple range test (DNMRT) at level 5%. The result of the research showed that the treatment of cow rumen compost10 ton.ha-1 and NPK fertilizer 900 kg.ha-1 gave better result on parameter of stem diameter, fruit length, fruit diameter, number of fruits per plant and fruit weight per m2.Keywords:cow rumen compost, NPK fertilizer, growth, red chili, yield